Leandro Ruiz (2011)
Leandro wanted to be a geologist, scientist or artist. In 2005 he entered EAFIT Children's University and now that he is 18 years old he is about to enter another university. He plans to study in France, but he wants to go back to Colombia, because he feels that his role, his place and his things are here.